Comparison of the Regulations Used in the Assessment of Vocational Permanent Disability Rates and Disability Rates - Eroğlu, İbrahim; Küpeli, Ahmet (The Bulletin of Legal Medicine, 2020)
The aim of this study was to emphasize the deficiencies of the scales under the regulation currently in use related to disability, to evaluate of the problems encountered by the experts according to the deficiencies, to draw attention to the necessity of a new regulation on international quality and to guide the new regulation. The disability reports which were prepared by Department of Forensic Medicine of  … University Medical Faculty between years of 2015-2016 were evaluated. The disability reports of the disability cases prepared using “The Scales of Measurement of Disabilities” were evaluated, the impairments related with disability were recalculated by “The Scale of Disability Rates”, and the ratios obtained using both scales were compared. There were 94 impairments in 49 cases detected as disability, the orthopedic impairments came into prominence among all of the impairments. There was no statistical significant difference between the rates calculated for the impairments of pelvis-lower extremities, head, face, vertebra, abdomen and ear according to “The Scales of Measurement of Disabilities” and “The Scale of Disability Rates” (respectively; p:0.241, 0.117, 0.083, 0.285, ~1, 0.317). The ratios of upper extremity and eye impairments obtained using both scales had statistically significant differences (respectively; p:0.002, 0.034). As a result, it was evaluated that it’s necessary the regulation and scales related to disability currently in use should be regulated to prepare more scientific, objective, reliable, persuasive and functional expert reports. It was assessed that “The Disability Rates Scale” could be used in evaluating the disability rate in the process.
Keywords: Forensic Science; impairment; expert; disability